2017
DOI: 10.1109/lca.2015.2512873
|View full text |Cite
|
Sign up to set email alerts
|

Cache Calculus: Modeling Caches through Differential Equations

Abstract: Abstract-Caches are critical to performance, yet their behavior is hard to understand and model. In particular, prior work does not provide closed-form solutions of cache performance, i.e. simple expressions for the miss rate of a specific access pattern. Existing cache models instead use numerical methods that, unlike closed-form solutions, are computationally expensive and yield limited insight. We present cache calculus, a technique that models cache behavior as a system of ordinary differential equations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For interested readers, our technical report[6] presents a detailed cache replacement MDP using a reference model from our recent work[8,9].…”
mentioning
confidence: 99%
“…For interested readers, our technical report[6] presents a detailed cache replacement MDP using a reference model from our recent work[8,9].…”
mentioning
confidence: 99%
“…Indeed, the access patterns that cause large errors-highly correlated references-are precisely those that cache well in the private cache levels. In other work, we have shown that this assumption is surprisingly robust, yielding accurate predictions even on access patterns that violate it [6]. Sec.…”
Section: Model Assumptionsmentioning
confidence: 75%
“…then the coarsened hit equation is: The model is unchanged under coarsening for a deep reason. Our model can be relaxed into a system of differential equations through some simple transformations [6]. From this perspective, coarsening is essentially a numerical solution of the system using an adaptive step size [43].…”
Section: Increased Step Sizementioning
confidence: 99%
“…Unfortunately, they often require low-level system details which are not available till late in the design cycle. In contrast, analytical models-simpler ones in particularabstract away these low-level system details and provide key insights early in the design cycle that are useful for experts and non-experts alike [2,5,19,27,48,54].…”
Section: Introductionmentioning
confidence: 99%